Efficacy of Two School-Based Interventions on Notational Ability of Bilingual Preschoolers: A Group-Randomized Trial Study - Incognito, Oriana; Bigozzi, Lucia; Vettori, Giulia; Pinto, Giuliana (Frontiers in Psychology, 2021)
This randomized trial study aimed to analyze the efficacy of two different school-based interventions - normal preschool literacy teaching, and the PASSI intervention carried out for different durations (12 weeks versus 30 weeks) - on notational knowledge of bilingual language-minority (BLM) preschoolers and their monolingual peers, after controlling their linguistic background and socio- economic status. A total of 251 children aged four-five years (M age= 4 years and 8 months; SD age= 6 months; 49% males, 51% females) were recruited from 19 classes in five preschools and randomly assigned to three groups that corresponded to different notational-focused interventions: (1) normal preschool literacy teaching (Condition 1; n=47); (2) the PASSI intervention carried out for 12 weeks (Condition 2; n= 119); and (3) the PASSI intervention carried out for 30 weeks (Condition 3; n=85). We collected two waves of data before and after the interventions regarding notational knowledge and phonological skills. Using the mixed ANOVA, we found that the PASSI intervention (both durations of 12 weeks and 30 weeks) led to a significantly higher level of notational knowledge in BLM children and their monolingual peers. In addition, we observed that with the PASSI intervention carried out for 30 weeks, the baseline difference between BLMs and their monolingual peers was nullified. This study demonstrates that well-designed, school-based programs can benefit language-minority children by supporting their emergent notational knowledge. This paper also discusses implications for bilingual education policymaking.